2005
DOI: 10.1007/s10038-005-0294-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of four Austronesian-speaking populations

Abstract: Ascertaining the genetic relationships between Austronesian populations is paramount to understanding their dispersal throughout the islands of the Pacific and Indian Oceans. The start of the Austronesian expansion has been dated to approximately 6,000 years ago, and from linguistic and archeological evidence, the origin of this dispersal may have been the island of Formosa. Consequently, the Taiwanese aboriginal populations and their phylogenetic relationship to the Austronesian-speaking groups from Madagasca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…However, the investigators also reported evidence of a prolonged isolation from mainland Chinese and other Asian influences in the recent past. Studies based on autosomal (Sewerin et al 2002;Chow et al 2005) and mtDNA (Horai et al 1995) markers have also demonstrated genetic uniqueness among the indigenous groups, implying varying temporal and/or spatial sources for the initial colonization of Formosa. One paternal lineage study found that the Ami stand out from the other aboriginal groups because of their closer genetic association with both South China and the Philippines.…”
Section: Discussionmentioning
confidence: 99%
“…However, the investigators also reported evidence of a prolonged isolation from mainland Chinese and other Asian influences in the recent past. Studies based on autosomal (Sewerin et al 2002;Chow et al 2005) and mtDNA (Horai et al 1995) markers have also demonstrated genetic uniqueness among the indigenous groups, implying varying temporal and/or spatial sources for the initial colonization of Formosa. One paternal lineage study found that the Ami stand out from the other aboriginal groups because of their closer genetic association with both South China and the Philippines.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Austronesian language-speaking populations tend to mimic, genetically, any non-Austronesian populations with which they are in contact, rather than presenting starkly contrasting genetic histories. This is true of all areas in which there are both Austronesian-speaking and non-Austronesianspeaking populations, including Madagascar, Southeast Asia, and Melanesia (Chow et al 2005;Hurles et al 2005;Li et al 2008). This implies that the genetic history of Austronesian speakers, in whichever region they are found, implicates the preexisting populations of these regions as much as any putative migration out of Taiwan.…”
Section: Human Population Geneticsmentioning
confidence: 92%
“…There were different clustering results for the tribes in Taiwan proper. However, Ami tribe located in the eastern portion of Taiwan separated from other tribes by Central Mountain Range is found to be relatively different from other tribes in Taiwan proper [17,18]. The Taiwanese Han population includes the descendants of individuals who migrated from China in a number of waves of immigration beginning 400 years ago and up to 1949.…”
Section: Introductionmentioning
confidence: 98%